Two tales: the army of ants,the powerful jinn - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
The first tale highlights the teamwork and organization of an army of ants working to survive. The second story explores the might and influence of a powerful jinn, emphasizing the themes of strength and responsibility.